Strategi Pembelajaran Kontekstual dalam Mengatasi Penurunan Kemampuan Berpikir Kritis Akibat Ketergantungan Media Sosial - Aliyah Yaasin; Dhini Andriani; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Dependence on social media among students has become a phenomenon that negatively impacts their critical thinking abilities, including difficulties in analyzing information, evaluating sources, and drawing logical conclusions. This study aims to examine contextual learning strategies as an effort to overcome the decline in critical thinking skills caused by social media dependence. The method used is a library research approach by reviewing various scientific sources such as books, journals, and previous studies relevant to contextual learning and critical thinking. The results of the study indicate that contextual learning can improve students’ critical thinking skills by linking learning materials to real-life situations, using authentic problems, and encouraging active student involvement in the learning process. This strategy promotes students to become more reflective, analytical, and independent in responding to information, including content obtained from social media. In addition, contextual learning helps students develop the ability to filter information and build deeper understanding. The implication of this study suggests that the consistent implementation of contextual learning strategies can serve as an effective solution to enhance students’ critical thinking skills and reduce the negative effects of social media dependence in the learning process.